A survey of attitudes of glaucoma subspecialists in England and Wales to visual field test intervals in relation to NICE guidelines. Issue 5 (3rd May 2013) - Malik, Rizwan; Baker, Helen; Russell, Richard A; Crabb, David P
Abstract : Objectives: To establish the attitudes of glaucoma specialists to the frequency of visual field (VF) testing in the UK, using the NICE recommendations as a standard for ideal practice. Design: Interview and postal survey. Setting: UK and Eire Glaucoma Society national meeting 2011 in Manchester, UK, with a second round of surveys administered by post. Participants: All consultant glaucoma specialists in England and Wales were invited to complete the survey. Primary and secondary outcome measures: (1) Compliance of assigned follow-up VF intervals with NICE guidelines for three hypothetical patient scenarios, with satisfactory treated intraocular pressure and (a) no evidence of VF progression; (b) evidence of VF progression and (c) uncertainty about VF progression, and respondents were asked to provide typical follow-up intervals representative of their practice; (2) attitudes to research recommendations for six VF in the first 2 years for newly diagnosed patients with glaucoma. Results: 70 glaucoma specialists completed the survey. For each of the clinical scenarios a, b and c, 14 (20%), 33 (47%) and 28 (40%) responses, respectively, fell outside the follow-up interval recommended by NICE. Nearly half of the specialists (46%) agreed that 6 VF tests in the first 2 years was ideal practice, while 16 (28%) said this was practice 'not possible', with many giving resources within the NHS setting as a limiting factor. Conclusions: The results from this survey suggest that there is a large variation in attitudes to follow-up intervals for patients with glaucoma in the UK, with assigned intervals for VF testing which are, in many cases, inconsistent with the guidelines from NICE.